2022
DOI: 10.1093/hr/uhac101
|View full text |Cite
|
Sign up to set email alerts
|

Chemical induction of leaf senescence and powdery mildew resistance involves ethylene-mediated chlorophyll degradation and ROS metabolism in cucumber

Abstract: Timely initiating leaf senescence is an integral part of plants’ development and importantly, an adaptive strategy for them to cope with various stresses, e.g. to limit the spread of pathogens. Powdery mildew is a major cucumber disease that promotes the initiation/progression of leaf senescence and reduces leaf photosynthesis, resulting in severe losses of yield and quality. However, how powdery mildew induces leaf senescence and how cucumber plants respond to enhance their resistance remain unclear. Here, wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 53 publications
0
11
0
Order By: Relevance
“…Similarly, the diacetyl treatment reduced the activities of ACS and ACO through inhibiting the expression of ethylene synthesis genes, such as BoACS1 , BoACS2 , BoACS3 , BoACO1 , BoACO2 , and BoACO3 , thereby further reducing ethylene generation in this study ( Figure 5 ). Moreover, some studies have shown that ethylene could regulate the transcription levels of genes encoding major chlorophyll degradation and ROS metabolism enzymes ( 47 , 48 ). For example, ethylene insensitive 3 (EIN3), a positive regulator of ethylene signaling, accelerated chlorophyll degradation by physically binding to NOL , NYC1 and PAO promoters to induce their expression.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the diacetyl treatment reduced the activities of ACS and ACO through inhibiting the expression of ethylene synthesis genes, such as BoACS1 , BoACS2 , BoACS3 , BoACO1 , BoACO2 , and BoACO3 , thereby further reducing ethylene generation in this study ( Figure 5 ). Moreover, some studies have shown that ethylene could regulate the transcription levels of genes encoding major chlorophyll degradation and ROS metabolism enzymes ( 47 , 48 ). For example, ethylene insensitive 3 (EIN3), a positive regulator of ethylene signaling, accelerated chlorophyll degradation by physically binding to NOL , NYC1 and PAO promoters to induce their expression.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al observed that powdery mildew and propabenzole (PBZ)-activated ethylene (ET) signal transduction, upregulates the expressions of CSEIN3 and CsCCGs and CsRBOHs, leads to leaf senescence, and improves the plant's resistance to powdery. An invading pathogen causes a "suicide" hypersensitivity reaction in leaves, which triggers a cascade of immune responses and a slow green loss phenomenon, which is indicative of the rapid aging process of cells (Zhang et al, 2022). Wang et al have also shown that cucumber anthrax and downy mildew resistance is directly regulated by NYE1/SGR1 .…”
Section: Genes Regulate Leaf Senescence and Horticultural Plant Yieldmentioning
confidence: 99%
“…It plays a role in signalling and regulating growth (Ehonen et al, 2019). However, excessive accumulation of ROS caused by environmental stress, metabolic disorders, or other stressful factors can lead to chloroplast damage, resulting in chloroplast dismantling (Bresson et al, 2018; Fan et al, 2021; Zhang et al, 2022; Guo et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…ROS can directly or indirectly damage the membrane structure of chloroplasts, reduce photosynthetic efficiency, and inhibit chlorophyll synthesis, leading to impaired chloroplast function and ageing. TOR signalling plays a crucial role in the development and function of chloroplasts (Song et al, 2021; Li & Kim, 2022; Zhang et al, 2022). By modulating the synthesis and degradation of chloroplast proteins, TOR can influence the morphology, quantity, and functionality of chloroplasts (Riegler et al, 2021; D'Alessandro, 2022).…”
Section: Introductionmentioning
confidence: 99%